Analysis of Digital Learning Models-based MOOCs in Practical Courses to Motivate Students to Learn in Higher Education - Rahmad Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze the need for developing digital knowledge models using MOOCs in practical courses to increase a literacy provocation in advanced education. This disquisition is a type of quantitative descriptive. The population taken in this study were all undergraduate and postgraduate scholars at a state Islamic university in  Curup. The slice fashion used is a probability slice with a total sample of 502 scholars from 18 study programs. The system used for data collection is a questionnaire. The instrument used in this studyis a questionnaire on the need for developing a digital knowledge model using MOOCs in practical courses to increase a provocation to learn in advanced education. The results of this study indicate that the instrument used is valid and reliable. The study results also stated that the scholars in this university agreed to develop a digital knowledge model using MOOCs in practical courses with a chance of 75,35%.